Ekonomi Syari'ah dalam Perspektif Pancasila - Jalil, Mat (Tapis: Jurnal Penelitian Ilmiah, 2018)
Sharia economics has been discussed lately, which is all lines call sharia. Islamic banks, sharia pawnshops, sharia insurance, sharia gold, scattered as if fight for sharia title, which is resulted in doubt into the sharia itself. Sharia economy have the complexity and complicated situations, when faced to market management phenomena and wider relugation as well as implications and solutions of sharia economy. Sharia economy in Pancasila perspective becomes important to be lifted with consideration that sharia economy growth in Indonesia, managed by many private sector, it shows where the position of state in this context along with widespread of decentralization issue. Public support for sharia economy is strengthening, sharia economy not just calling or spreading syaria in his efforts but requires the provisions of the Qur'an and Hadith. Economic concepts practically relate to various issues, political, legal, social, cultural, religious and so forth. economic enforcement adopted by the Indonesian people ideologically refers to Pancasila which means incorporating the values of Pancasila in it.